2012
DOI: 10.1158/1535-7163.mct-12-0311
|View full text |Cite
|
Sign up to set email alerts
|

Activation of IL-6R/JAK1/STAT3 Signaling Induces De Novo Resistance to Irreversible EGFR Inhibitors in Non–Small Cell Lung Cancer with T790M Resistance Mutation

Abstract: The secondary T790M mutation in epidermal growth factor receptor (EGFR) is the major mechanism of acquired resistance to EGFR tyrosine kinase inhibitors (TKI) in non-small cell lung cancer (NSCLC). Although irreversible EGFR TKIs, such as afatinib or dacomitinib, have been introduced to overcome the acquired resistance, they showed a limited efficacy in NSCLC with T790M. Herein, we identified the novel de novo resistance mechanism to irreversible EGFR TKIs in H1975 and PC9-GR cells, which are NSCLC cells with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 50 publications
10
155
0
Order By: Relevance
“…[26][27][28] An increased autocrine stimulation of the IL-6/STAT3 pathway could unleash the cells from their dependency on EGFR. 27) Notably, increased levels of IL-6 was reported in around 30% of NSCLC patients and in EGFR-TKI treated cell culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] An increased autocrine stimulation of the IL-6/STAT3 pathway could unleash the cells from their dependency on EGFR. 27) Notably, increased levels of IL-6 was reported in around 30% of NSCLC patients and in EGFR-TKI treated cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Since EMT has been previously reported to be associated with erlotinib resistance and IL-6 activation was reported as a key mechanism underlying EGFR-TKI resis- tance, 11,[26][27][28][29] We examined the IL-6 secretion of HCC827-ER cells. Culture supernatant from HCC827-ER cells contained significantly higher levels of IL-6 as compared with parental cells.…”
Section: Acquired Resistance Of the Egfr-tki Inhibitor Erlotinib In Hmentioning
confidence: 99%
“…These results reinforce the need for 2 nd and 3 rd generation EGFR TKIs, while taking into account existing data that suggest use of erlotinib or gefitinib beyond progression, with added chemotherapy, radiotherapy or best supportive care may improve survival 19 . Although afatinib and dacomitinib have been introduced to overcome acquired resistance, they showed limited efficacy in NSCLC with T790M and were more than 100-fold less potent in NSCLC cells with EGFR T790M mutation than in NSCLC cells with EGFR activating mutation 20 . CO-1686 is a novel covalent inhibitor that irreversibly and selectively targets both the initial activating EGFR mutations and the T790M secondary acquired resistance mutation 21 .…”
Section: Systemic Treatment In Egfr-alk Nsclc Patients: Second Line Tmentioning
confidence: 99%
“…It may be the cause leads to STAT3 activation upon TKI treatment. Recently, a study had been reported that lung cancer cell lines with secondary EGFR mutation showed de novo resistance to irreversible EGFR inhibitors through induction of IL-6R/JAK1/STAT3 upon afatinib treatment (41).…”
Section: Discussionmentioning
confidence: 99%